Would Ronald Coase love Bitcoin? : How Blockchain Lowers Transaction Costs and Changes the Coasian Firm - Kaid, Amira (2016)
The rising popularity of blockchain technology otherwise known as the technology that underlies the Bitcoin protocol has been the subject of a lot of investigation and enthusiasm among financial organizations for its potentially revolutionary properties that will likely change how the economy works in the future. The blockchain is a decentralized open source ledger that records bitcoin transactions and is maintained by a distributed network of miners. Blockchain technology however has many applications beyond currency and can be applied in various areas including the firm organizational structure and law. This thesis examines how blockchain technology would lower the transaction costs involved in organizing the firm and how it would thus change the role of the firm. Coase (1937) in his article (The Nature of the Firm) explained that firms exist and continue to operate in a hierarchal manner because of the transaction costs that are involved in using the market mechanism. This paper also examines how the blockchain would lower the transaction costs of resolving disputes through carrying out market transactions that were mentioned by Coase (1960) in (The Problem of Social Cost). In order to achieve this aim Coases framework is used to theoretically model a future firm and legal system which are blockchain-based and that use bitcoin in their transactions. The results indicate that blockchain technology would reduce the transaction costs pointed out by Coase in such a way that it would cause the firm to become less hierarchal in nature and would allow it to adopt a more inclusive and distributed management system. Similarly in the case of law the transaction costs would fall making it easier for parties to resolve their disputes using the market mechanism instead of having to rely on a central authority.